Change and continuity in Asymmetric Alliances in the Asia Pacific: Japanese and Australian security alliances with the Unites States of America - Kemppainen, Sampo (fi=Turun yliopisto|en=University of Turku|, 2021)
This dissertation examines the development of military alliances in the Asia-Pacific after the end of the Cold War. The research focuses on US alliances with Japan and Australia and tracks the central developments in these two alliances since the late Cold War period until the end of the 2010s. The research is designed as a comparative case study of these two alliance relations. The research framework is constructed around four theoretical approaches to military alliances derived from the Realist School of International Relations: the framework of threats, the alliance security dilemma, the influence of domestic politics on alliances and, lastly, the asymmetric alliance framework. This study provides comprehensive and historical parallel narratives of the two alliances. The developments in the alliances are considered from the perspectives of institutional and political structures, international military operations, defense procurement, and technological cooperation. The cases are divided into three periods that are designed to roughly correspond to the different dynamics of power relations in the region, beginning from the period of uncontested US unipolarity in the Asia-Pacific and ending with the increased military rivalry in the region and the rise of China. While different theoretical frameworks are determined to have their own strengths and weaknesses, the longer time perspective used in this study clearly demonstrates that the asymmetric nature of these alliances is simply the strongest explanatory factor behind the persistent lines of development witnessed in the alliances. These long-term trends are, in turn, consistently found to explain several singular events better than short term focus on more immediate factors such as changing domestic circumstances. The asymmetric framework has arguably been underutilized in the contemporary International Relations discipline, but the results of this work show that it can provide valuable insights for future research on military alliances, especially given the nature of today’s world, characterized by increasingly fluid power relations.

Tämä väitöstyö käsittelee Aasian ja Tyynenmeren alueen sotilasliittojen kehittymistä kylmän sodan päättymisen jälkeisenä aikana. Tutkimus keskittyy Yhdysvaltojen sotilasliittoihin Japanin ja Australian kanssa ja seuraa niiden keskeisiä kehityslinjoja kylmän sodan viimeisistä vuosista aina 2010-luvun loppupuolelle. Tutkimus on suunniteltu vertailevaksi tapaustutkimukseksi näiden kahden liittosuhteen välillä. Tutkimuksen viitekehys rakentuu kansainvälisen politiikan Realismin tutkimus-perinteestä johdettuihin neljään keskeiseen sotilasliittojen tutkimuksen malliin. Nämä ovat uhkien, liittodilemman, valtion sisäpolitiikan ja asymmetristen sotilasliittojen teoreettiset viitekehykset. Työ tarjoaa kokonaisvaltaisen historiallisen narratiivin sen kohteena olevista sotilasliitoista. Sotilasliittojen kehitystä käsitellään institutionaalisten rakenteiden, kansainvälisten sotilasoperaatioiden sekä puolustushankintojen ja teknologisen yhteistyön kautta. Tapaustutkimukset on jaettu kolmeen ajanjaksoon, jotka on määritelty vastaamaan Aasian-Tyynenmeren alueen kansainvälisen järjestelmän voimasuhteissa tapahtuneita muutoksia, alkaen Yhdysvaltojen kiistattoman taloudellisen ja sotilaallisen valta-aseman kaudesta 1990-luvun alussa ja päättyen 2010-luvun kiihtyvän sotilaallisen vastakkainasettelun ja nousevan Kiinan aikaan. Tutkimus löytää sekä vahvuuksia että heikkouksia kaikista neljästä käytetystä teoreettisesta viitekehyksestä. Kuitenkin, pidemmällä aikaperspektiivillä tarkasteltuna, sotilasliittojen asymmetristä luonnetta painottava viitekehys selittää selvästi parhaiten liittojen pitkään jatkuneita kehityslinjoja. Pitkän linjan kehityslinjat puolestaan selittävät myös yksittäiset tapahtumat vakuuttavammin kuin lyhemmällä tähtäimellä muuttuvat tekijät, kuten valtioiden sisäiset poliittiset olosuhteet. Asymmetristä viitekehystä ei ole aiemmin kattavasti käytetty sotilasliittojen tutkimuksessa. Tämän tutkimuksen tulosten valossa on kuitenkin selvää, että viitekehyksen kautta voidaan saada arvokasta tietoa Aasian-Tyynenmeren alueen sotilasliittojen mahdollisista kehityslinjoista. Tällainen tieto on erityisen arvokasta nykyisen, nopeasti muuttuvan kansainvälisen voimatasapainon aikana.